Mechanisms to control the problem of Bank credit default in the light of international experiences - An analytical study - Fakhari, Farouk; Zebiri, Nora (Finance and Business Economies Review, 2019)
The objective of this article is to study and analyze the problem of Credit default in the banks that are operating on the international and local level, where the most important mechanisms used to control the problem of Stumbling and to analyze its effectiveness. The study reached several conclusions, The most important one is that the excessive credit granting without accurate credit studies is one of the most important pillars of the problem of Stumbling , The study also showed the great role of various government policies as well as monetary authorities and the financial institutions in containing the phenomenon of Credit default that are operating globally and at the level of Algerian commercial banks.